Pedagogies for peace, the relevance of the gender approach and the intersectionality - Amézquita Aguirre, Luisa; Trimiño Velásquez, Celina (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of this article is to research some developments in pedagogies for peace and their joint with theories that challenge patriarchy. Its originality lies on connecting the dissertation of pedagogies for peace, the relevance of the gender approach and intersectionality that impels the limits of exclusive epistemologies to be overflowed, to move towards alternative proposals. The qualitative-interpretative method helps the use of documentary analysis strategies to analyze the theories that contribute with other assumptions to highlight the diversity of human beings and to denounce the multiple oppressions that different community spaces are subjected for different reasons, which lead to trying to justify their exclusion from public and decision-making spaces, and in several countries even to their physical removal, which violates their human rights. This dynamic of theoretical exploration allows us to conclude that approaching pedagogies for peace is a permanent exercise that involves both educational curriculum and actions of our daily life, a task that requires a joint effort from the whole of Colombian society for the consolidation of a stable and lasting peace.